PEMBUATAN DAN PENGUJIAN KUALITAS KOMPOS DI SUBAK TIBUBIYU KECAMATAN KERAMBITAN KABUPATEN TABANAN - I.W. Narka; I.N. `Dibia; T. Kusmawati; I.W.D. Atmaja (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
Devotion in the form of training of composting with existing materials around the farmers using 3 starter thatis EM4, MOL and Nitrobacter TJ has been done in Subak Tibubiyu, Kerambitan Tabanan. After subsequentcomposting is testing the quality of the three types of compost produced. The topic of composting andcompost quality testing is selected based on the farmers' demand because it is pointed out by the organicfertilizer farmers that the packaging is obtained in the form of aid, the quality is not good. Is a problem alsoin terms of transport to the planting area? Therefore, it is necessary to make compost near the farmer'scultivation area. In improving the quality of compost has been tried to make compost with 3 types of starterand then done the quality of compost testing. Farmers welcomed this activity and were interested to find outwhich type of starter was best composted. After fermentation for 6 weeks the compost has matured, then thequality of the compost is tested. The results of compost testing in the laboratory show that the best compostquality is compost with EM4 starter. With the success of farmers to make their own good quality compostfertilizer, the acceleration of organic fertilizer will be done. The use of compost fertilizer can reduce the useof chemical fertilizers and maintain the sustainability of the soil.